Excel 2016 all-in-one for dummies - Harvey, Greg (Hoboken, New Jersey : John Wiley & Sons, 2016)
Excel has undergone a massive makeover, and each of the mini-books in this guide covers one important area of Excel 2016. If you're new to Excel, Harvey covers all the essentials, then branches out into information on worksheets, charts and graphs, and ways to maintain and analyze the data you create.
Introduction -- Excel basics -- Worksheet design -- Formulas and functions -- Worksheet collaboration and review -- Charts and graphics -- Data management -- Data analysis -- Macros and VBA.
"8 books in 1"--Cover.
Includes index.
Description based on print version record.
Electronic reproduction. Ann Arbor, MI : ProQuest, 2016. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: Microsoft Excel (Computer file); Electronic spreadsheets -- Computer programs; Business -- Computer programs; Electronic books